(untitled) (Journal of the Bangladesh Agricultural University, 2010)
The study was undertaken to identify the constraints of native cattle genetic resource conservation at the farm level along with their features of breeding system and profitability. Five different study sites like south-west, northern hills, industrial zone, north-west and mid-region were selected representatively from all over the country. A total of 280 cattle farmers from the selected regions were interviewed. A multiple regression model was fitted to know the impact of contributing factors on lactation characteristics of cows. The double log linear model was also used to explore the input-output relationship of milk production. Average milk yield was 1.78 and 5.64 liter per day per cow respectively for native and crossbred cow. Contribution of age, order of lactation and stage of lactation were predictable in native cattle but not in crossbreds. Livestock farming contributed 36.4 percent of total income of the farmers studied. A crossbred cattle farming was profitable but native cattle farming was non-profitable. Indigenous cattle were preferred over crossbred due to their superior adaptability to local environmental stresses, rearing ease, low input, lesser proneness to disease and availability of native bull for mating. Per farm average number of milch cow was found to be reduced day by day and maximum number was 4 in a farm during the period 2006-07. Major causes of reduction were the non-profitability, crisis of feed, lack of investment, introduction of exotic breed etc. Responded farmers had no clear idea on conservation of native cattle. Keywords: Genetic resource; Conservation; Breeding system; Profitability assessment DOI: 10.3329/jbau.v8i1.6407 J. Bangladesh Agril. Univ. 8(1): 113-120, 2010